2016
DOI: 10.1177/1054773816652085
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Testing of an Instrument About Intimate Partner Violence

Abstract: This study used step-by-step exploratory factor analysis in the framework of confirmatory factor analysis (EFA/CFA) to evaluate the psychometric properties of the translated and culturally adapted Swedish version of "The Violence Against Women Health Care Provider Survey." The Swedish version of the instrument was needed to measure district nurses' preparedness to encounter women exposed to intimate partner violence. In the first step of EFA/CFA, the eight-factor model was confirmed. The item-total correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Method phase I Development of REAGERA-P The first draft of the REAGERA-P was developed by the first author. It was inspired by two previous instruments in Swedish that are used to measure health care provider preparedness to care for victims of intimate partner violence of all ages [36][37][38]. Questions were, however, revised to better reflect clinical encounters with older adults.…”
Section: Phase 1: Development and Validity Testmentioning
confidence: 99%
“…Method phase I Development of REAGERA-P The first draft of the REAGERA-P was developed by the first author. It was inspired by two previous instruments in Swedish that are used to measure health care provider preparedness to care for victims of intimate partner violence of all ages [36][37][38]. Questions were, however, revised to better reflect clinical encounters with older adults.…”
Section: Phase 1: Development and Validity Testmentioning
confidence: 99%
“…Some of the district nurses trained as educators may have found it difficult to educate the other district nurses at their workplaces, as both the role and the topic were new to them. IPV is an emotionally demanding topic, and it may require time to come to terms with these emotions and to feel more confident with newly acquired information about IPV . Additionally, support from organisational leaders is crucial to achieving change .…”
Section: Discussionmentioning
confidence: 99%
“…It is important that district nurses look for and can find professional support when they encounter women exposed to IPV. Both in Sweden and elsewhere , research has shown that professional support facilitates nursing care for women exposed to IPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation